The incidence of Facebook overuse in the academic performance of freshman students at the Foreign Languages Department of the University of el Salvador during semester I/2013 - Fuentes Gudiel, Rolando Francisco
Facebook overuse causes an impact on the academic performance. Students of the Foreign Language Department communicate and network with each other through Facebook, in some cases more than the normal face-to face communication. Among the variety of Social Networks sites, students prefer to use Facebook because they are able to freely express their thoughts and their feelings. There are over 500 million active users on its website every month in El Salvador. The problem is that students appear to be using Facebook excessively and during times when they should be working on coursework or studying. Facebook affects student‟s academic scores. University students in this study have grades that are compiled into an overall grade point average (GPA) and therefore, academic performance will be determined by the student„s college cumulative GPA and grades along as unit. Long hours spent on Facebook decrease student‟s academic performance and thus their grades. Students are aware that the web site is a distractor and time consuming; most of them consider that they cannot live without checking Facebook profile at every moment because they like it and some of them are addicted to it. This addiction causes distraction while they are in class or doing their academic tasks. Therefore, this research perceives the effects on student‟s achievements and physiological effects on the basis of flow theory and the cognitive absorption on Facebook. The goal of this study is to gather information about freshman student‟s Facebook use and to analyze the incidence between Facebook use and academic performance.